Mechanical, thermal, and viscoelastic investigations on expanded perlite–filled high-density polyethylene composite. (December 2018) - Atagür, Metehan; Sarikanat, Mehmet; Uysalman, Tuğçe; Polat, Ozan; Elbeyli, İffet Yakar; Seki, Yoldaş; Sever, Kutlay
Perlite is a glassy amorphous volcanic rock and generally used in construction industries. Possible uses of perlite powder in polymeric composites allow producing value-added products. In this study, expanded Turkish perlite (TP) powder was characterized by particle size distribution and Brunauer–Emmett–Teller analysis. TP-filled high-density polyethylene (HDPE) composites were manufactured via thermokinetic mixer by adding various weight fractions of TP powder (5, 10, 20, and 30 wt%) into HDPE matrix. Produced composites were characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, dynamic mechanic analysis, X-ray diffraction, and mechanical and thermal conductivity tests. From mechanical tests, it was observed that HDPE + 5% TP exhibited the greatest tensile strength. Flexural strength of the TP-filled HDPE composite was increased with the increasing TP content. Morphological properties of TP-filled HFPE composites were examined by scanning electron microscopy. As the weight fraction of TP was increased, storage modulus and loss modulus of the composites were increased. Moreover, the relaxation peak of HDPE was increased by the incorporation of TP into HDPE.